Roles of Acyl-CoA. Issue 5 (May 2015) - Li, Chen; Li, Lena; Lian, Jihong; Watts, Russell; Nelson, Randal; Goodwin, Bryan; Lehner, Richard
<x xml:space="preserve">Abstract</x> Objective— Very low–density lipoprotein assembly and secretion are regulated by the availability of triacylglycerol. Although compelling evidence indicates that the majority of triacylglycerol in very low–density lipoprotein is derived from re-esterification of lipolytic products released by endoplasmic reticulum–associated lipases, little is known about roles of acyl-CoA:diacylglycerol acyltransferases (DGATs) in this process. We aimed to investigate the contribution of DGAT1 and DGAT2 in lipid metabolism and lipoprotein secretion in primary mouse and human hepatocytes. Approach and Results— We used highly selective small-molecule inhibitors of DGAT1 and DGAT2, and we tracked storage and secretion of lipids synthesized de novo from [3H]acetic acid and from exogenously supplied [3H]oleic acid. Inactivation of individual DGAT activity did not affect incorporation of either radiolabeled precursor into intracellular triacylglycerol, whereas combined inactivation of both DGATs severely attenuated triacylglycerol synthesis. However, inhibition of DGAT2 augmented fatty acid oxidation, whereas inhibition of DGAT1 increased triacylglycerol secretion, suggesting preferential channeling of separate DGAT-derived triacylglycerol pools to distinct metabolic pathways. Inactivation of DGAT2 impaired cytosolic lipid droplet expansion, whereas DGAT1 inactivation promoted large lipid droplet formation. Moreover, inactivation of DGAT2 attenuated expression of lipogenic genes. Finally, triacylglycerol secretion was significantly reduced on DGAT2 inhibition without altering extracellular apolipoprotein B levels. Conclusions— Our data suggest that DGAT1 and DGAT2 can compensate for each other to synthesize triacylglycerol, but triacylglycerol synthesized by DGAT1 is preferentially channeled to oxidation, whereas DGAT2 synthesizes triacylglycerol destined for very low–density lipoprotein assembly.